Efficacy of Monoclonal Antibodies Against Calcitonin Gene-Related Peptide for Medication Overuse Headache in Migraine Patients: Literature Review - A. Kairytė; P. Lukoševičius; G. Žemgulytė (Neurologijos seminarai)
Medication overuse headache (MOH) is a type of headache that is caused by an excessive use of pain-relief medication, most commonly in individuals with migraine. This condition negatively impacts the quality of life of those affected, while also placing a significant socioeconomic burden on the healthcare system. Over the past decade, preventive treatment has become a lot more prominent in the management of MOH in an attempt to reduce the risk of medication overuse. Although medication groups such as antidepressants, beta-blockers, and antiepileptics are still being used for preventive treatment, more recent and specific treatments, namely, monoclonal antibodies against calcitonin gene-related peptide (CGRP), are being increasingly applied. This review article discusses the epidemiology and risk factors of MOH as well as the latest clinical studies investigating the efficacy of monoclonal antibodies against CGRP in treating MOH in patients suffering from migraine.